Under the big-ice: fluid-ice structure interaction of the Drygalski ice tongue - Edwards, C; Alexander Forrest; Zhi Quan Leong; Yun, S; Lee, WS (2016)
The Drygalski Ice Tongue (DIT) is the largest floating glacier in Antarctica, extending approximately 120km into McMurdo Sound, and exhibits a significant influence upon the prevailing northward current, as the ice draft of the majority of the DIT is greater than the depth of the observed well-mixed surface layer. This influence is difficult to characterize using conventional methods such as in-situ LADCP measurements, vertically collected profiles or long term moorings as these are generally relatively spatially sparse datasets. In order to better relate measurements across the entire region of influence of the DIT region, a set of Computational Fluid Dynamics (CFD) simulations were conducted using a generalized topography of a mid-span transect of the DIT. CTD and LADCP measurements made in close (<100 m) proximity of the DIT were used as boundary conditions for the model. These measurements revealed a layered structure in the water column typical of the region, with salinities varying from 34.3 g/kg at the surface to 34.81 g/kg at approximately 1200 m depth. The degree of mixing and the associated sharpening of the pycnocline varied greatly over the observation period of 4 days. The CFD work, using Large Eddy Simulation (LES) for a homogeneous two-layer water column independently produced an estimated region of influence of the ice structure approximately 3km and 7km upstream and downstream of the DIT respectively for a given flow regime. Numerical modeling of environmental flows around ice structures advances the knowledge of the fluid dynamics of the system in not only the region surrounding the DIT but also provides a clearer insight into fluid-ice structure interactions and heat flux in the system. This may lead to a better understanding of the long-term fate of floating glaciers.